Pengaruh Layanan dan Keamanan Transaksi Terhadap Kepuasan Pengguna Mobile Banking BYOND by BSI: (Studi Pada Masyarakat Kalangan Usia Produktif Kerja Di Kabupaten Purwakarta) - Apriansyah, Muhamad Suhendri; Sucipto, Moch. Cahyo; Arsyad, Dea (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2025)
This study was motivated by the increasing use of digital Islamic banking services, especially among the productive age group who demand convenience, speed, and security in transactions. However, the BYOND by BSI mobile banking application still faces a number of obstacles, such as transaction failures due to system disruptions or unstable connections, as well as user concerns about the security of personal data, including account information and transaction history. The purpose of this study is to determine the effect of service and transaction security on the satisfaction of BYOND by BSI mobile banking users among the productive working age population in Purwakarta Regency. The research method used a descriptive quantitative approach with a population of the productive working age population in Purwakarta Regency. The sampling technique used convenience sampling with 43 respondents, while data analysis used validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, correlation coefficient, and coefficient of determination (R²) tests. The results showed that the service variable had a positive and significant effect on user satisfaction, as evidenced by a t-value > t-table (6.517 > 2.021) and significance (0.000 < 0.05), with an R² value of 0.509. The transaction security variable also has a positive and significant effect on user satisfaction, with tcount > ttable (6.323 > 2.021), significance (0.000 < 0.05), and an R² value of 0.494. Simultaneously, service and transaction security affect user satisfaction with an Fcount > Ftable (21.856 > 3.23), significance (0.000 < 0.05), and a coefficient of determination R² of 0.522, which means that both variables contribute 52.2% to user satisfaction. The conclusion of this study confirms that service quality and transaction security are important factors in increasing BYOND by BSI mobile banking user satisfaction. The impact of this study is expected to provide strategic input for banks in improving digital service quality, strengthening security systems, and increasing customer trust and loyalty, especially among the productive age group.